Hubungan Father Involvement dengan Psychological Well Being pada Remaja di MAN 1 Padang - Tasya Maharini; Dewi Fitriana; Mardenny (STAI AL-AMIN, 2026)
Psychological well-being is an important indicator in adolescent development because it is related to an individual's ability to accept themselves, establish positive relationships, have life goals, and manage developmental pressures adaptively. One factor that plays a role in shaping adolescent psychological well-being is father involvement, which is believed to have an important contribution to adolescent parenting and psychological well-being. This study aims to determine the relationship between father involvement and psychological well-being in adolescents at MAN 1 Padang. This study uses a quantitative approach with a correlational method. The subjects of this study were 269 students of MAN 1 Padang who were selected using purposive sampling. Data collection used the Psychological Well-Being scale short version and the father involvement scale. Data analysis was performed using descriptive statistics and Pearson Product Moment correlation tests. The results showed that the level of psychological well-being among adolescents was in the moderate category (60%), while father involvement was in the high category (57%). The correlation test shows a significant positive relationship between father involvement and psychological well-being (p < 0.05) with a contribution of 0.422. These findings indicate that the higher the father's involvement in parenting, the higher the psychological well-being of adolescents. This study confirms the importance of the father's role in supporting the psychological development of adolescents.